2021
DOI: 10.3390/insects12110999
|View full text |Cite
|
Sign up to set email alerts
|

Host Plant Species Mediates Impact of Neonicotinoid Exposure to Monarch Butterflies

Abstract: Neonicotinoids are the most widely used insecticides in North America. Numerous studies document the negative effects of neonicotinoids on bees, and it remains crucial to demonstrate if neonicotinoids affect other non-target insects, such as butterflies. Here we examine how two neonicotinoids (imidacloprid and clothianidin) affect the development, survival, and flight of monarch butterflies, and how these chemicals interact with the monarch’s milkweed host plant. We first fed caterpillars field-relevant low do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
2
5
0
Order By: Relevance
“…This is also not the first time that M. sativa and A. canadensis have been compared with this butterfly, and these findings (with respect to host plant effects on caterpillar performance) are consistent with past studies that have used different sources of plant material [44,48]. In addition to general nutritional quality, another motivation for this work was the possibility of interactions between a pesticide and secondary metabolites, given both hosts produce distinct phytochemical defences that can impact all the butterfly responses we measured [62] and interactions between host and pesticides have been observed in at least one other butterfly [28]. However, we only find simple, additive effects of these factors, which were highly lethal but not synergistic in action.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is also not the first time that M. sativa and A. canadensis have been compared with this butterfly, and these findings (with respect to host plant effects on caterpillar performance) are consistent with past studies that have used different sources of plant material [44,48]. In addition to general nutritional quality, another motivation for this work was the possibility of interactions between a pesticide and secondary metabolites, given both hosts produce distinct phytochemical defences that can impact all the butterfly responses we measured [62] and interactions between host and pesticides have been observed in at least one other butterfly [28]. However, we only find simple, additive effects of these factors, which were highly lethal but not synergistic in action.…”
Section: Discussionsupporting
confidence: 87%
“…When considering multiple stressors, even butterflies, the most widely studied of all major insect groups, suffer from a paucity of research. In experimental settings, interactions between host plant species and pesticide exposure have been demonstrated in monarch butterflies (Danaus plexippus), where caterpillars that experience high neonicotinoid exposure on low cardenolide milkweed species experience reduced survival and smaller body size compared to other treatment combinations [28]. Relative to the few studies investigating interactions with pesticides, controlled studies testing for interactions between temperature and host plant are slightly more common and have identified cases of interaction between diet and climate [29,30] and cases where an interaction is either not detected or is weak compared to additive effects [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Across three research groups, monarch colonies, and milkweed species, chronic exposure to clothianidin concentrations of 47–205 ng per g leaf caused 30%–50% larval mortality (Bargar et al 2020 , Olaya-Arenas et al 2020a , Krishnan et al 2021b ). Consistent with observations in Bargar et al ( 2020 ), Krishnan et al ( 2020 , 2021b) , and Prouty et al ( 2021 ) found that pupal ecdysis was disrupted in larvae exposed to clothianidin treatments. Knight et al ( 2021 ) found that larvae chronically exposed to leaf concentrations of 7–21 ng per g clothianidin had 3% mortality, whereas Olaya-Arenas et al ( 2020a ) found chronic exposure to 15 ng per g did not affect larval survival.…”
Section: Evaluating Risks Of Pesticide Use To Milkweed and Monarchssupporting
confidence: 88%
“…The current study further suggested the involvement of endophytic soil microbes associated with the host plant. In the case of the monarch butterfly, larval sensitivity to neonicotinoid insecticides seems to be influenced by which host plant species larvae feed on [114]. These cases imply that the biological effects of any pollutants should be evaluated in the context of ecological interactions among plants, animals, and microbes.…”
Section: Discussionmentioning
confidence: 99%